2014
DOI: 10.1016/j.ijscr.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic diagnosis and treatment of a hydrocele of the canal of Nuck extending in the retroperitoneal space: A case report

Abstract: HighlightsHydrocele of the canal of Nuck in the adult female is a rare condition.Laparoscopic diagnosis is useful for groin mass connected with the retroperitoneal space.TEP offers a useful alternative in selected patients with hydrocele of the canal of Nuck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Matsumoto et al wrote that patients who underwent TEP reported shorter recovery time and were at less risk of bowel adhesion formation [5]. They also argued that the TEP approach could provide surgeons with information on the origin and type of hydrocele in the canal of Nuck.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al wrote that patients who underwent TEP reported shorter recovery time and were at less risk of bowel adhesion formation [5]. They also argued that the TEP approach could provide surgeons with information on the origin and type of hydrocele in the canal of Nuck.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocele of canal of Nuck may be misdiagnosed as inguinal hernia because of its rarity, lack of clinician's knowledge regarding this entity and paucity of the relevant literature in the surgical textbooks. Furthermore at least one third of the cases are associated with inguinal hernia and most of the cases reported in the literature were diagnosed at surgery performed for suspicious inguinal hernia [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical dissection must be done up to the deep inguinal ring along with high ligation of the neck of the peritoneal pouch. Laparoscopy was also used for diagnosis as well as treatment of this entity [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to 7 of the included studies, no recurrence of the lesion was reported in the follow up period, which ranged from 2-24 months after surgery (3,8,9,16,18,20,22). Data concerning hospital stay was reported in 4 studies with a range of 20-72 h (7,10,18,20).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Several reports of cysts of the Canal of Nuck are presented in literature and describe the symptomatology and surgical approaches used in their treatment (7)(8)(9)(10). Although a rare pathology of the inguinal canal in female patients, it should be considered when diagnosing inguinal tumours in female patients.…”
Section: Introductionmentioning
confidence: 99%